Enhancing the Supervisory Board of the Corruption Eradication Commission: Insights from Hong Kong, United Kingdom, and European Union - Lutfi, Mustafa; Ramadhita, Ramadhita; Septiani, Septiani; Nur, Asrul Ibrahim (Faculty of Law, Universitas Sebelas Maret, 2023)
Establishing the KPK Supervisory Board as a juridical consequence of Law Number 19 of 2019 is an effort to improve KPK's supervisory system. But its formation has caused many pros and cons in the community. The existence of this board is considered to weaken and hinder the performance of KPK. This study analyzes the position of the KPK Supervisory Board after Constitutional Court Decree Number 70/PUU-XVII/2019 concerning reducing the pro-Justitia authority of the Supervisory Board regarding the comparative study involving several countries. This study uses legal research with comparative and statutory approaches. The study results show that the KPK Supervisory Board, as the KPK's internal supervisory body, still requires adjustments by adopting the supervisory mechanisms implemented by comparator countries relevant to the Indonesian Legal System. Some of these are related to the mechanism of monitoring and evaluation of the performance of the KPK Supervisory Board and the KPK itself.